Molecular authentication of sika deer (Cervus nippon) based on allele-specific PCR - Feixia Hou; Jihai Gao (Mitochondrial DNA. Part B. Resources, 2019)
Sika deer (Cervus nippon) is listed as a tonic in many ancient Chinese pharmaceutical. Many adulterants of sika deer products have been found in Chinese medicinal materials markets, which led to detrimental impacts in clinical treatment. However, it is lack of the rapid and effective identification method for sika deer. This study amplified 574 bp fragment of mtDNA COI region of 19 samples from seven Cervidae species, and the relevant five sequences from reindeer (Rangifer tarandus) were downloaded from GenBank. It was found that there were two SNP loci for sika deer. Phylogenetic analysis indicated that individuals from sika deer clustered together. Based on SNP locus, one pair specific primer for allele-specific PCR identification of sika deer was designed, which could be used to rapidly and accurately identify sika deer.